Analysis of Electrocardiograms by Digital Computer - Pipberger, H. V. (Methods of Information in Medicine, 1962)
A method for automatic analysis of the P-QRS-T complex of the electrocardiogram by means of digital computers has been described. Three corrected orthogonal ECG leads (FRANK system) are recorded simultaneously on magnetic analog tape. Consequently the data are converted into digital form with a sampling rate of 1,000/sec. In this form records are fed into a digital computer. A number of analytical computer programs for ECG analysis have been developed. Application of these methods to large samples of normal and abnormal records showed that parameters of spatial direction exceeded largely those of magnitude when diagnostic recognition rates were compared. Thus, application of ECG leads which lend themselves to accurate spatial analysis appear mandatory for any improvement of electrocardiography as a diagnostic tool.